Application Of Wondershare Filmora Interactive Mulitimedia Learning To Improve Sociology Leraning Outcomes For Students At State SMA 10 Gowa - Iskandar, Abdul Malik; Jalal, Jalal; Amir, Arfenti; Kasim, Hasanudin; Reski Salemuddin, Muh; Sriwahyuni, Sriwahyuni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research aims to determine (1) the application of video-based interactive multimedia learning media assisted by the Wondershare Filmora application in sociology learning at SMA Negeri 10 Gowa, and (2) improving student learning outcomes through video-based interactive multimedia learning media assisted by the Wondershare Filmora application in sociology learning. in senior high school. This research uses Classroom Action Research (PTK). The research objects are Class X students of SMA Negeri 10 Gowa. Data sources in this research are interviews, observations, tests and documentation. The data in this research were analyzed using descriptive quantitative statistical analysis. Based on the research that has been carried out, the results obtained (1) through the application of Wondershare Filmora media can help teachers create interesting, unique and interactive learning media in the classroom learning process. (2) Based on the results of the first cycle and second cycle tests, 35 students were declared to have met the KKM. This research has implications for the application of videobased interactive multimedia learning media, learning in the classroom takes place actively and interactively, students appear more enthusiastic and motivated to pay attention to what is displayed and explained directly by the teacher. This can certainly improve student learning outcomes, especially in Sociology subjects for students at SMA Negeri 10 Gowa.